2008
DOI: 10.1177/0960327108095993
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of the immune function of pesticide workers, a European wide assessment

Abstract: In this study, the prolonged low-dose exposure of mixtures of pesticides has been examined on hematological parameters and components of the immune defense in occupationally exposed humans. This investigation was carried out in five field studies in: the Netherlands (flower bulb growers, mainly re-entry workers), Italy (vineyard workers), Finland (potato farmers), and Bulgaria (workers from a zineb factory and greenhouse workers). Immunotoxicity was studied by measuring hematological parameters, compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The majority of available was in place with prolonged exposure or higher levels of exposures may occur. Other studies investigated the harmful effect of pesticides on the immune system as a European wide study which described minimal changes of the immune markers as detected in the current study [22]. However, this study was not studying specifically CYP but included other pesticides as well.…”
Section: Ijomeh 2017;30(4)mentioning
confidence: 89%
“…The majority of available was in place with prolonged exposure or higher levels of exposures may occur. Other studies investigated the harmful effect of pesticides on the immune system as a European wide study which described minimal changes of the immune markers as detected in the current study [22]. However, this study was not studying specifically CYP but included other pesticides as well.…”
Section: Ijomeh 2017;30(4)mentioning
confidence: 89%
“…Finally, acute poisoning from direct pesticide exposure is a considerable risk for agricultural workers. Although the impact of this exposure pathway is debated in North America and Europe (71,72), accidental exposure and deliberate misuse of agrochemicals seem more frequent in developing countries (73)(74)(75), resulting in an estimated poisoning of 3 million people with as many as 20,000 unintentional deaths per year (76).…”
Section: Global Pesticide Consumptionmentioning
confidence: 99%
“…Exposure to the synthetic pyrethroid cypermethrin, tended to lower the immunoglobulins (IgG, IgM, IgA), the complement components C3c and C4 and the acute phase protein α-acid glycoprotein (AAG), and the lymphocyte subpopulations CD3 + , CD4 + and CD20 + after pest control operation [ 10 ]. Steerenberg et al [ 11 ] found increased complement and IgG4 levels, but decreased IgA in European pesticide workers in agriculture who were exposed to a mixture of pesticides including ethylenebisdithiocarbamate (EBDC) fungicides. Chemical plant workers chronically exposed to pesticide dusts including captan and carbendazim showed disturbances in humoral and cellular immunities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%